Dynamic succession of the quantity and composition of epiphytic microorganisms at different growth stages on rice surface - Huang, Lijuan; Zhang, Zhifei; Mu, Lin; Liu, Xiong; Sun, Rongji; Gao, Wenjing; Chen, Guihua (Frontiers in Microbiology, 2024)
The quality of silage is uneven, which is due to the difference of epiphytic microorganisms of raw materials. To improve the quality of fermentation, the quantity and composition of epiphytic microorganisms are usually analyzed to better prepare silage. In this research, plate coating method and 16S high-throughput sequencing were used to analyze the differences in the quantity and composition of rice epiphytic microorganisms during different growth stages. The Lactic acid bacteria (LAB) and aerobic bacteria were the highest at the flowering stage, the yeast was the highest at the milk ripening stage, and the mould was the highest at the full ripening stage. And the growth stage also had a great influence on the composition of epiphytic bacterial community, at the phylum level, it was mainly composed of Proteobacteria. And at the genus level, Pantoea, Acinetobacter, Pseudomonas and Chryseobacterium were dominanted at the flowering stage; Pantoea, Stenotrophomonas and Sphingobacterium were dominanted at the milk ripening stage; Acinetobacter, Pantoea, Chryseobacterium and Lactococcus were dominanted at the dough stage; Acinetobacter and Klebsiella were dominated at the full ripening stage. Overall, the growth stage significantly affected the quantity and composition of rice epiphytic microorganisms. Therefore, rice silage can be modulated reasonably according to the number and composition of epiphytic microorganisms in different growth stages.